Comparison of Chemical Profiles of Aronia melanocarpa Fruit Extracts - Eda Sönmez Gürer; Ayşe Esra Karadağ; Ayhan Altıntaş (Turkish Journal of Agriculture: Food Science and Technology, 2023)
The chokeberry plant, which is native to North America and the south of Canada, is a deciduous, shrub-shaped, berry-like plant belonging to the Rosaceae family, which survives for many years. It is seen as a plant that adapts easily to almost every climatic condition and soil and has many beneficial properties for health. Within the scope of this study, methanol, 70% ethanol, ethanol, ethyl acetate, hexane and water extracts were prepared from the fruits collected from the Aronia melanocarpa (Michx.) Elliott plant, which is cultivated in the Kırklareli region. The chemical contents of the obtained extracts were clarified by high performance liquid chromatography. It was determined that phenolic compounds such as ferulic acid, caffeic acid, quercetin, quercetin-3-galactoside, p-coumaric acid were found in the extracts, and ethyl acetate extract was found to have the richest phenolic substance profile. Malvin anthocyanin compound was detected only in methanol extract.